An investigation into how Grade 7 Natural Science teachers mediate learning through code-switching from English to Silozi in the Zambezi region of Namibia : a case study - Denuga, Hildred Malilo (Rhodes University, Faculty of Education, Department of Education, 2015)
The Namibian government's language policy for schools has opted for English as the official language of education. But the use of English in Namibian schools has nevertheless presented certain challenges. Although the Ministry of Education has chosen English as the language of instruction from upper primary (Grade 4) up to the tertiary level, it has been found that English proficiency is poor among both learners and teachers. It is against this backdrop that this study sought to investigate how Grade 7 Natural Science teachers mediate learning through code-switching from English to Silozi in the Zambezi Region of Namibia. The study explored Natural Science teachers' perceptions and experiences of code-switching, how they and their learners make sense of concepts in science classes when code-switching is applied, and lastly, how code-switching from English to Silozi enables or constrains learning in Natural Science classes. The main question is: How do Grade 7 Natural Science teachers mediate learning through code-switching from English to Silozi? A qualitative case study underpinned by an interpretive paradigm was carried out at Zebra School (pseudonym) in the Zambezi Region of Namibia with two participant teachers. My unit of analysis was mediation of learning through code-switching, and data were obtained from lesson observations, questionnaires, interviews and document analysis. A variety of data gathering technique was employed for triangulation purposes to enhance the validity and trustworthiness of the data. During the data analysis process, data were grouped into common themes and subsequently organized into analytical statements in relation to the research questions. It was found that code-switching was widely employed in Grade 7 Natural Science classes in the Zambezi Region. It was also found that teachers code-switch to help learners understand the subject content, to explain concepts, to emphasize points and to include learners' participation in the subject. The findings also revealed that some few teachers were against code-switching because examinations are written in English and the language policy does not recommend code-switching. Notwithstanding this, since the majority of teachers do code-switch to support their learners' understanding in science classes, I recommend that education curriculum planners should include code-switching in the curriculum guidelines, and that the practice should be officially acknowledged as a legitimate strategy for teachers.
Keywords: Science -- Study and teaching (Elementary) -- Namibia -- Case studies; Code switching (Linguistics); Language and education